2005
DOI: 10.1051/0004-6361:20042496
|View full text |Cite
|
Sign up to set email alerts
|

FIRST-based survey of Compact Steep Spectrum sources

Abstract: Abstract.A new sample of candidate Compact Steep Spectrum (CSS) sources that are much weaker than the CSS source prototypes has been selected from the VLA FIRST catalogue. MERLIN "snapshot" observations of the sources at 5 GHz indicate that six of them have an FR II-like morphology, but are not edge-brightened as is normal for Medium-sized Symmetric Objects (MSOs) and FR IIs. Further observations of these six sources with the VLA at 4.9 GHz and MERLIN at 1.7 GHz, as well as subsequent full-track observations w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 47 publications
(52 reference statements)
4
31
0
Order By: Relevance
“…If the supply of new relativistic particles turns off, the radio emission fades rapidly due to the severe energy losses and the radio spectrum steepens fast making these sources under-represented in flux-limited catalogues. Indeed, only a few objects have been suggested as faders so far, based on the absence of active regions (Kunert-Bajraszewska et al 2005, and the distribution of spectral index found steep across the whole source, like in the case of PKS 1518+047 (Orienti, Murgia, & Dallacasa 2010). A different situation is the recurrence of the radio emission in an AGN.…”
Section: The Life-cycle Of the Radio Emissionmentioning
confidence: 99%
“…If the supply of new relativistic particles turns off, the radio emission fades rapidly due to the severe energy losses and the radio spectrum steepens fast making these sources under-represented in flux-limited catalogues. Indeed, only a few objects have been suggested as faders so far, based on the absence of active regions (Kunert-Bajraszewska et al 2005, and the distribution of spectral index found steep across the whole source, like in the case of PKS 1518+047 (Orienti, Murgia, & Dallacasa 2010). A different situation is the recurrence of the radio emission in an AGN.…”
Section: The Life-cycle Of the Radio Emissionmentioning
confidence: 99%
“…The sample has been studied in detail in a series of 5 papers, devoted to the study of the morphology of the objects on different angular scales, using MERLIN and VLA on large scale (Kunert et al 2002;Kunert-Bajraszewska et al 2005), MERLIN and EVN/VLBA for smaller sources (Marecki, Kunert-Bajrasze 2006), and the VLBA for the most compact objects (Kunert-Bajraszewska, Mare 2006;Kunert-Bajraszewska & Marecki 2007). In total, images have been presented for 46 sources, including 11 MSOs.…”
Section: First-based Survey(s) Of Css Sourcesmentioning
confidence: 99%
“…With one exception (1201+394) they have asymmetric structures. The remaining six objects are double or triple MSOs and were presented in Kunert-Bajraszewska et al (2005) -hereafter Paper II.…”
Section: The First-based Css Sources Samplementioning
confidence: 99%